Soundscapes and the Live Music Culture of Madison, WI - Stewart, Zachary; Leininger, Megan; Royalty, Jesse (My University, 2012)
A city's "downtown" is often characterized by entertainment, and Madison is no different. It is a music hub of nightly live performances that brings together a broad demographic range of people and performers. Our research breaks down how the performance landscape, associated soundscape, and the audience interact and overlap to influence each other and create Madison's music scene. We interviewed owners and managers at The Rathskeller, the Frequency, and the High Noon Saloon, and attended multiple shows to take detailed participant observation notes. Over a span of 4 months we passed out surveys asking specific questions about audience preferences of each venue. Using these methods, we found that Madison?s regional location between larger cities like Milwaukee, Chicago, and the Twin Cities attracts large national acts already touring, but leaves room for local talent to be showcased. The Internet plays a growing role in booking tactics, attendance rates, and marketing. Seasonal variation in listener rates directly affects quality and quantity of performances. We found that most venues do not have target demographics, but try to appeal to all Madisonians. The differences in design at each venue create a variety of social experiences that offer something for everyone.
Includes Graphics, Observation notes, Interview notes, Photographs, Appendices, Maps, Figures and Bibliography.
Keywords: Live Music; Madison, WI